2019
DOI: 10.1038/s41592-019-0493-9
|View full text |Cite|
|
Sign up to set email alerts
|

Kilohertz frame-rate two-photon tomography

Abstract: Point-scanning two-photon microscopy enables high-resolution imaging within scattering specimens such as the mammalian brain, but sequential acquisition of voxels fundamentally limits its speed. We developed a two-photon imaging technique that scans lines of excitation across a focal plane at multiple angles and computationally recovers high-resolution images, attaining voxel rates of over 1 billion Hz in structured samples. Using a static image as a prior for recording neural activity, we imaged visually-evok… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
142
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(144 citation statements)
references
References 65 publications
2
142
0
Order By: Relevance
“…7a). Previous work showed that 300 µm below the pia, brief stimulation (1 ms, 500 µA) of NB elicits punctate (<2 µm) and rapid (~10 ms) iAChSnFR transients, consistent with synaptic ACh release events 38 . Here we compared dynamics of stimulationevoked ACh transients recorded from neuropil at different cortical depths in response to pulse trains of different lengths (1, 3, or 10 pulses at 20 Hz).…”
Section: Kilohertz Imaging Of Cortical Acetylcholine Releasesupporting
confidence: 53%
See 2 more Smart Citations
“…7a). Previous work showed that 300 µm below the pia, brief stimulation (1 ms, 500 µA) of NB elicits punctate (<2 µm) and rapid (~10 ms) iAChSnFR transients, consistent with synaptic ACh release events 38 . Here we compared dynamics of stimulationevoked ACh transients recorded from neuropil at different cortical depths in response to pulse trains of different lengths (1, 3, or 10 pulses at 20 Hz).…”
Section: Kilohertz Imaging Of Cortical Acetylcholine Releasesupporting
confidence: 53%
“…The sensor is based on a bacterial choline-binding protein, and it shows no apparent effects on neurons following stable expression in rodent brain slice and in living worms, fish, flies, and mice -both in the brain and at the neuromuscular junction (NMJ). We further created both green and yellow variants, the latter enabling kilohertz frame-rate imaging in mouse cortex in vivo with SLAP microscopy 38 . The sensor also allows detection of both increases and decreases of acetylcholine signaling from tonic levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the operation of these circuits has been greatly advanced by using multiphoton microscopy to image fluorescent reporter proteins that signal events such as changes in cytoplasmic calcium, reflecting spiking activity (Tian et al, 2012), or the release of glutamate at excitatory synapses (Marvin et al, 2013). At present, the large majority of in vivo imaging studies quantify activity as calcium signals in the soma of neurons but we also need to image activity across populations of synapses if the operations of neural circuits are to be unravelled (Lu et al, 2017;Kazemipour et al, 2019;Meng et al, 2019). These connections are key components of all the computations within neural circuits and sites at which neuromodulators act to reconfigure signal flow according to changes in the internal state of the animal.…”
Section: Introductionmentioning
confidence: 99%
“…High-power industrial light sources such as Ytterbium-doped fiber lasers (YbFLs) and modelocked semiconductor lasers show great promise to overcome these limitations, as they have increasingly shown feasibility for in-vivo applications [2][3][4][5][6][7] and are becoming widely available at costs orders of magnitude lower and/or power outputs orders of magnitude higher than conventional tunable lasers ( Supplementary Fig. 1).…”
mentioning
confidence: 99%